Brief Pain Inventory and McGill Pain Questionnaire in Assessing the Patients with Temporomandibular Joint Disorders – A Cross-Sectional Study - Keerthana Selvam; J Anand Kumar; Suman J. Lakshmi; Senthil Kumar Balasubramanian (Journal of Indian Academy of Oral Medicine and Radiology)
Background: The temporomandibular joint, where the mandible articulates with the skull, is renowned for its complexity. Temporomandibular disorders (TMDs) are the second most prevalent musculoskeletal affliction, causing pain and disability, underscoring their impact on well-being. Objective: To assess the efficacy of the Brief Pain Inventory and McGill Pain Questionnaire in TMD pain evaluation. Material and Methods: This study included 100 patients diagnosed with TMD who were asked to complete two questionnaires: the Brief Pain Inventory and the McGill Pain Questionnaire; the responses provided by the patients were collected and subjected to statistical analysis. Results: Among a cohort of 100 patients, the mean values for the duration and intensity of pain associated with TMD using Brief Pain Inventory manifested statistical significance, underscored by a P value of 0.001. The mean values of the Pain Rating Index and Present Pain Intensity, as determined through the McGill Pain Questionnaire across the study population, exhibited statistical significance, registering a P value of 0.001. Conclusion: The Brief Pain Inventory is most useful when compared with the McGill pain questionnaire in assessing the pain in patients with TMD.